The Influence of Transformational Leadership Style, Work Environment, and Compensation on Employee Work Motivation at CV. Laba Ayu - Tegar Pramana Adi Putra I Wayan; I Gusti Ngurah Widya Hadi Saputra; Wirsa I Nengah; Winda Yanti Ni Kadek (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
CV Laba Ayu is a company engaged in the pork slaughtering business, which involves physical labor processes. In this work, employee motivation is very important for the smooth production and distribution processes. Based on observations and initial interviews with several employees, a decline in work motivation was found among CV Laba Ayu workers. The purpose of this study was to determine the variables of leadership style, work environment, and compensation related to work motivation at CV Laba Ayu. The type of research used in this study is associative quantitative research, which explores the relationship between two or more variables. The population in this study were all employees working at CV Laba Ayu. The results of the study indicate that CV Laba Ayu leaders must be able to improve their transformational leadership style so that it can increase the work motivation of the employees who work with them. A good work environment will also have an impact on employee motivation to complete the tasks assigned to them. In this case, motivation given to employees in the form of a stable monthly salary and facilities that support the implementation of employee work are also available